Genetic Algorithm for Improving Route of Travelling Salesman Problem Generated by Savings Algorithm - Muhammad Ardhya Bisma; Ekra Sanggala (Sainteks: Jurnal Sain dan Teknik, 2023)
Travelling Salesman Problem (TSP) is the problem for finding the shortest route starting from start node then visiting number of nodes exactly once and finally go back to start node. If a TSP has a lot of nodes, it will be a NP-Hard Problem. Algorithms working based on heuristic and metaheuristic can be a solution for solving NP-Hard Problem. Savings Algorithm is a heuristic algorithm, so it’s solution may be not the best solution, therefore there is a chance to improve it. Genetic Algorithm is a metaheuristic that can be applied on many optimization problems, including TSP. This paper will discuss about GA for improving route TSP generated by Savings Algorithm. On testing of 10 instances, showing that algorithm based on GA can improve route of TSP generated by Savings Algorithm.